2017
DOI: 10.3892/mco.2017.1390
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive treatment of unresectable cardiac angiosarcoma: A case report and review of literature

Abstract: Abstract. Cardiac angiosarcoma is a rare but lethal tumor that is difficult to diagnose and treat, due to its rapid local relapse and high incidence of systemic metastasis. The prognosis of cardiac angiosarcoma is dismal, with a mean life expectancy of only a few months. We herein report a case of unresectable angiosarcoma arising from the right atrium. The patient received first-line chemotherapy with weekly paclitaxel, and second-line therapy with vinorelbine and bevacizumab upon disease progression. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previously, the concurrent use of chemotherapy and RT to treat cardiac sarcomas has been described in small case reports 1 . Only one report of a patient with undifferentiated pleomorphic sarcoma of the left atrium has been reported to receive PBT alone to the primary tumor during one of the many relapses 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the concurrent use of chemotherapy and RT to treat cardiac sarcomas has been described in small case reports 1 . Only one report of a patient with undifferentiated pleomorphic sarcoma of the left atrium has been reported to receive PBT alone to the primary tumor during one of the many relapses 2 .…”
Section: Discussionmentioning
confidence: 99%
“…No unified standard for AS chemotherapy currently exists, but research suggests that cytotoxic drugs such as platinum, doxorubicin, paclitaxel, and methotrexate may benefit patients not eligible for radical surgery [ 22 ]. Advancements in oncology and immunology have led to the emergence of tumor immunotherapy as an anti-tumor approach, complementing surgery, radiotherapy, and chemotherapy [ 23 ]. A study analyzing 106 cutaneous AS cases found a correlation between PD-1/PD-L1 expression and AS progression, suggesting that anti-PD-1 antibody therapy could be a potential novel treatment [ 24 ].…”
mentioning
confidence: 99%